2014
DOI: 10.4322/rbeb.2014.004
|View full text |Cite
|
Sign up to set email alerts
|

Study of advanced rheumatoid arthritis

Abstract: Introduction: Rheumatic diseases are considered public health problems affecting millions of people worldwide resulting in high and rising health-care costs. In this work, Fourier Transform Infrared spectroscopy associated to Partial Least Square regression (PLS) analysis was used to diagnose rheumatoid arthritis (RA) from human serum. Methods: The sera of 94 individuals were collected, which included 47 from rheumatic patients and 47 from healthy individuals. The results from PLS analysis were compared to sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 73 publications
(75 reference statements)
0
6
0
7
Order By: Relevance
“…Rheumatoid arthritis (RA) is one of the most prevalent autoimmune and degenerative joint diseases with immune hyperactivation and synovitis ( 1 , 2 ). Non-steroidal anti-inflammatory drugs (NSAIDs), disease-modifying antirheumatic drugs (DMARDs), and glucocorticoids are the most commonly used drugs for the clinical treatment of RA ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is one of the most prevalent autoimmune and degenerative joint diseases with immune hyperactivation and synovitis ( 1 , 2 ). Non-steroidal anti-inflammatory drugs (NSAIDs), disease-modifying antirheumatic drugs (DMARDs), and glucocorticoids are the most commonly used drugs for the clinical treatment of RA ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies demonstrated high sensitivity of FT-IR to analyze the skeletal muscle (Jerônimo et al, 2012), heart muscle (Cheheltani et al 2012), and some biological fluids, such as serum (Carvalho et al, 2014), urine (Khaskheli et al, 2013), and saliva (Khaustova et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…O valor do pH crítico depende da solubilidade dos tecidos duros e da concentração cálcio, fosfato e flúor na solução, pois estes minerais determinarão o grau de saturação da solução e consequentemente direcionarão para a perda ou precipitação mineral, quando a solução se apresentar subsaturada ou supersaturada, em relação ao produto de solubilidade das apatitas dentárias (LUSSI et al, 2011). Soluções ácidas (pH<5,5) com cálcio na sua composição em concentrações maiores que as encontradas no fluido da placa (3,5-8,2mmol CARVALHO, 2014). No presente estudo, a concentração de cálcio variou de 0,289 a 0,501 mmmol/L valores muitos baixos para exercer algum efeito protetor, especialmente nas pastilhas com pH abaixo de 5,5, como observado em alguns produtos analisados neste estudo.…”
Section: Discussionunclassified